New Application of G′/G-Expansion Method for Generalized (2+1)-Dimensional Nonlinear Evolution Equations. (16th May 2013) - Najafi, Mohammad; Najafi, Maliheh; Arbabi, Somayeh
Abstract : We establishedG ′ / G -expansion method for (2+1)-dimensional nonlinear evolution equations. This method was used to construct travelling wave solutions of (2+1)-dimensional nonlinear evolution equations. (2+1)-Dimensional breaking soliton equation, (2+1)-dimensional Calogero-Bogoyavlenskii-Schiff (CBS) equation, and (2+1)-dimensional Bogoyavlenskii's Breaking soliton equation are chosen to illustrate the effectiveness of the method.